THE ROLE OF UREA LIME MIXTURE IN CONCENTRATE CONTAINING DIFFERENT LEVELS OF CASSAVA ON RUMEN FERMENTATION OF ETAWAH CROSSBRED GOAT - O. Cakra, I G. L.; Sudana, I. B.; Mahardika, I G.; G. Partama, I. B. (E-Journal of Animal Science Udayana University, 2013)
An experiment was carried out to study to the role of urea lime mixture in concentrate containing cassava on the rumen fermentation of the etawah crossbred goat through in-vivo experiment. A randomized block design (RBD) consisted of 4 different rations and 4 replicates was used in this experiment. Atotal of 16 etawah crossbred goats with initial body weight ranging from 12.4 - 19 kg were aranged in to 16 pens experiment. Four feed treatments (A, B, C and D) were offered to four groups of four goats. The first treatment (A) was 50% elephant grass 50% concentrate (without cassava urea lime) as control diet, the second treatment (B) was 50% elephant grass 50% concentrate (without cassava, with 4% urea and 2% lime), the third treatment (C) was 50% elephant grass 50% concentrate (with 25% cassava, 4% urea and 2% lime), and fourth treatment (D) was 50% elephant grass 50% concentrate (with 50% cassava, 4% urea and 2% lime). Ration was composed based on standard requirement of 15 kg body weight goat with 75 g daily weight gain. Results of This study showed that the concentration of NH3, VFA, propionic acid, and protozoa rumen population on treatment A, B, C, and D were significantly different (p<0,05). It can be concluded that Utilization of 4% urea and 2% lime without cassava in concentrate increased N-NH3 level of rumen fluid, but level of N-NH3 rumen fluid on goat fed with 4% urea and 2% lime in concentrate contain 25 and 50% cassava was not increase, compared to thoset fed controled (treatment A). Propionic acid level and rumen protozoa population could be increased through urea lime and cassava addition in concentrate.
Keywords: urea-lime, cassava, rumen fermentation, etawah crossbred goat